Asymmetric synthesis of cyclopropanes - Ambler, P (1988)
This thesis is concerned with the asymmetric synthesis of cyclopropyl derivatives via the use of chiral iron acyl complexes of the type (η5-C5H5)Fe(CO)(PPh3)(COCH=CR'R), Chapter 1 reviews previous routes to optically active cyclopropyl derivatives and reviews the use of the chiral auxiliary (η5-C5H5)Fe(CO)(PPh3) for asymmetric synthesis. Chapter 2 describes the synthesis of the complexes (η5-C5H5)Fe(CO)(PPh3)(COCH=CRR') and presents a conformational analysis of the α, β-unsaturated acyl ligand. Chapter 3 describes the diastereoselective synthesis of cis- substituted cyclopropyl complexes via the reaction of Z-α, β-unsaturated iron acyl complexes with electrophilic alkylidene species. Decomplexation, to give the corresponding cyclopropyl esters, occurred without epimerisation of the cyclopropane ring. By the use of homochiral iron acyl complexes the enantioselective synthesis of cyclopropyl derivatives was achieved. Section A describes methylene addition and Section B isopropylidene addition reactions. Section C describes attempts to synthesise pyrethroid insecticide precursors which occurred with good diastereoselectivity but poor regioselectivity. Section D describes electrophilic ethylidene addition reactions in which the chiral auxiliary exerts good stereochemical control over three new chiral centres. Chapter 4 describes the diastereoselective synthesis of trans- substituted cyclopropyl complexes via the reaction of E-α, β-unsaturated iron acyl complexes with nucleophilic alkylidene transfer reagents. Section A describes methylene transfer reagents. Whilst α-lithiosulphides and α-lithiosulphoxides were of limited use, iodomethyllithium (generated in situ) resulted in highly diastereoselective syntheses of the cyclopropyl complexes. Decomplexation, to give the corresponding cyclopropyl esters, occurred without epimerisation of the cyclopropane ring. By the use of homochiral iron acyl complexes the enantioselective synthesis of cyclopropyl derivatives was achieved. Section B describes the generation of 1-iodoethyllithium and 1-iodobutyllithium and their reactions as nucleophilic alkylidene transfer reagents. The stereo- chemistry at two of the new chiral centres is controlled by the iron chiral auxiliary, whilst that at a third is controlled by a number of factors.